Sexist Language and Its Impact on Second Language Learning - Agung Tri Wahyuningsih (Universitas Bunda Mulia, 2017)
This article discusses the issue of language used in classroom as medium of teacher-students communication related to sexism in linguistic expression. This discussion is scooped on merely theoretical overview on sexist language which then is connected to the process of second language acquisition. This article is triggered by a statement that is very disturbing that a female student keeps using the word “he” to refer to herself. What has happened to her language learning process? This article tries to reveal possibility in discovering that problem. The result shows that teacher holds very important role in creating environment that learners possess their second language. When a teacher keeps using a certain language, learners imitate the teacher’s habit of only using certain words. So that teacher’s language choice should be seen as something important. Keywords: second language acquisition, sexist language, teacher, environment.